Synthesis of a Glycosylphosphatidylinositol Anchor Derived from Leishmania donovani That Can Be Functionalized by Cu-Catalyzed Azide–Alkyne Cycloadditions - Ding, Ning (Org Lett, 2017)
A flexible assembly strategy has been developed for the synthesis of Leishmania donovani GPI anchors that bear a clickable alkyne tag. This strategy is based on the use of the 2-naphthylmethyl (Nap) ethers and levulinoyl (Lev) ester for permanent protection of hydroxyls. Removal of seven Nap ethers by 2,3-dichloro-5,6-dicyano-1,4-benzoquinone made it possible to prepare GPIs having an alkyne functionality that could be modified by Cu(I)-catalyzed [3 + 2] cycloadditions to install tags for imaging studies.